The New Zealand Trusts Bill: an overview of proposed reforms. Issue 9 (6th September 2018) - Alexander, Jack; Burnett, Callum
Abstract: The New Zealand Parliament is considering a new Trusts Bill that replaces old legislation governing trusts. It is the most extensive change in the trusts landscape in New Zealand in 60 years. The Trusts Bill does more than express the former legislation in modern terms—it also includes substantive changes to the law; in some parts enacting, and others replacing, the existing requirements of common law. This article provides an overview of the Bill in its current form. It focuses on the most significant changes and offers comment on aspects of the Bill that could be further refined before it is enacted.